Using contextual information in the evaluation of the effectiveness of barriers restricting access to the main line at stations - Wronska, Urszula; Ryan, Brendan (2017)
The use of fencing at railway stations to reduce the numbers of fatalities is a common safety intervention. This study examines the effectiveness of a mid-platform fencing programme as a means of preventing access to the track area. Two aspects of the programme are considered: firstly the extent to which fencing has been fitted to provide a secure barrier to fast lines at the target stations; and secondly, investigation of incidents in which the physical barrier has been overcome by individuals. The study involved the analysis and collation of descriptive data, using station visits, interviews with industry staff, examination of reports on the incidents and data from the SMIS database. It was found that the desired level of restriction of access to the intended areas through fencing was not always provided. So far, there have been few examples where somebody attempted or succeeded in climbing over a barrier to access the track. Factors affecting the effectiveness of physical barriers are presented and some shortcomings in current collection of evidence through incident reporting are highlighted.